2010
DOI: 10.1007/s00531-010-0540-3
|View full text |Cite
|
Sign up to set email alerts
|

A Late Jurassic–Early Cretaceous metamorphic core complex, Strandja Massif, NW Turkey

Abstract: In the eastern part of the Strandja Massif constituting the east end of the Rhodope Massif, the amphibolite facies basement rocks intruded by Permian metagranites are juxtaposed against the greenschist facies cover metasediments of Triassic-Middle Jurassic protolith age. The distinct metamorphic break between the basement and cover rocks requires a missing metamorphic section. The boundary between the two groups of rocks is a ductile to brittle extensional shear zone with kinematic indicators exhibiting a top … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(13 citation statements)
references
References 39 publications
0
13
0
Order By: Relevance
“…Because this platform seals the accretion and obduction history and related tectono-metamorphic history of the eastern Vardar Zone and Circum-Rhodope Belt ophiolites, it provides stratigraphic constraint for the latest Jurassic-earliest Cretaceous Balkan orogenic event in both tectonic units. This constraint has strong implication for the regional consistency of the Balkan tectonic event also recorded between 162 and 134 Ma in the adjacent Strandzha Zone (Okay et al, 2001;Elmas et al, 2011;Sunal et al, 2011;see Fig. 1), as well as for Kraishte zone which overlies the Serbo-Macedonian Massif northerly, where the same event was recorded between 146 and 130 Ma (Kounov et al, 2010).…”
Section: Regional Extent Of the Earliest Cretaceous Carbonate Platformentioning
confidence: 86%
“…Because this platform seals the accretion and obduction history and related tectono-metamorphic history of the eastern Vardar Zone and Circum-Rhodope Belt ophiolites, it provides stratigraphic constraint for the latest Jurassic-earliest Cretaceous Balkan orogenic event in both tectonic units. This constraint has strong implication for the regional consistency of the Balkan tectonic event also recorded between 162 and 134 Ma in the adjacent Strandzha Zone (Okay et al, 2001;Elmas et al, 2011;Sunal et al, 2011;see Fig. 1), as well as for Kraishte zone which overlies the Serbo-Macedonian Massif northerly, where the same event was recorded between 146 and 130 Ma (Kounov et al, 2010).…”
Section: Regional Extent Of the Earliest Cretaceous Carbonate Platformentioning
confidence: 86%
“…Natal'in et al (2016) interpreted this boundary as a thrust, but we regard it as a low-angle normal fault, because it in places elides in the entire Triassic section. This normal fault may have been coeval with those that opened the Luda Kamčija Trough just to the north during the Pliensbachian-Toarcian interval in which deposition commenced with the Sinivir Formation (Tchoumatchenco et al 1992), although Elmas et al (2011) reported a considerable late Jurassic-early Cretaceous ( 40 Ar/ 39 Ar ages between 156 to 143 Ma) extension leading to the formation of an extensional metamorphic core complex in the northeastern Strandja. These two extensional events may be one protracted episode or two successive episodes of extension.…”
Section: Rhodope-pontide Fragmentmentioning
confidence: 98%
“…111 Ma [21,22,[24][25][26][27]. Similar late-Jurassic to early Cretaceous ages are also documented from the eastern part of the Strandja Zone, where a two-stage process of ductile and brittle deformation is documented by Elmas et al, [57], between ca. 156 and ca.…”
Section: Geotectonic Implications Of the Apatite And Titanite Agesmentioning
confidence: 68%